State of digitalization of seed companies and quality declared seed producers in Tanzania - Chima, Richards; Kibaza, Areth; Mutua, Mercy; Ngomuo, Munguatosha; Radegunda, Kessy; Kalemera, Sylvia; Ojiewo, Christopher Ochieng; Rubyogo, Jean Claude; Ochieng, Justus; Nassari, Peter; Tlankka, Nicodemus (2025)
Digital transformation holds vast potential for advancing sustainable agriculture in the Global South, yet significant gaps remain in sectors such as Tanzania’s seed industry, which plays a critical role in agricultural productivity and food security. This study examines the current level of digital adoption among Tanzanian seed companies and Quality Declared Seed (QDS) producers, focusing on three value chains: common beans, sorghum, and groundnuts. Using survey data from 148 QDS producers and all registered 30 seed companies, collected by the Tanzania Official Seed Certification Institute (TOSCI), we assess the current state of digital use by these entities and how digital technologies can contribute to improved market access, customer engagement, and operational efficiencies. Our analysis highlights the uneven engagement between seed companies and QDS producers, value chain disparities, and persistent barriers such as limited device access, low digital literacy, and restricted awareness of digital tools. Understanding these differences in digital engagement is essential for developing effective strategies that can bridge the digital divide and create inclusive digital transformation pathways for all actors in Tanzania’s seed sector.